DETERMINAN INVESTASI PENANAMAN MODAL DALAM NEGERI (PMDN) DI INDONESIA - Yunus, Frisnawati; Rostin, Rostin; Rumbia, Wali Aya (JPEP (Jurnal Progres Ekonomi Pembangunan), 2019)
The purpose of this study is to analyze how the effect of Product Domestic Bruto, Goverment Expenditure, Interest Rate, Inflation and Excange Rate on Domestic Investment in Indonesia. The type of reseacrh is quantitative. The type of data is secondary. The data used is time series from 1988-2017. The analysis method was the Error Correction Modhel (ECM).  The result of the study to show that: 1). Product Domestic Bruto is positive not significantly effect; 2). Goverment ekspenditure is positive significantly effect; 3) Interes Rate is possitive significantly effect; 4). Inflation is negative significantly effect; 4). Exchange Rate is negative significantly effect.  Keywords:        Product Domestic Bruto, Goverment Expenditure, Interest Rate, Inflation, Exchange Rate and Domestic Investment.